807Association between diabetes and adjuvant chemotherapy implementation among patients with stage III colorectal cancer. (2nd September 2021) - Kanehara, Rieko; Goto, Atsushi; Watanabe, Tomone; Inoue, Kosuke; Taguri, Masataka; Kobayashi, Satoshi; Imai, Kenjiro; Saito, Eiko; Katanoda, Kota; Iwasaki, Motoki; Ohashi, Ken; Noda, Mitsuhiko; et al.
Abstract: Background: Preexisting diabetes may contribute to the indication for adjuvant chemotherapy among patients with colorectal cancer (CRC); however, the association between diabetes and its implementation is largely unknown. Methods: We analyzed the hospital-based cancer registry and health claims data of patients with stage III CRC who received curative surgery in 2013 in Japan (n = 6, 344). Chemotherapy and diabetes was identified based on procedure, prescription, and diabetes codes in claims data. We examined the association between diabetes and implementation rate of adjuvant chemotherapy using the generalized linear model adjusted for age, sex, and updated Charlson Comorbidity Index, hospital type, and prefecture. We further applied a mediation analysis to examine the extent to which postoperative complications mediated the association. Results: Of these, 1, 236 (19.5%) had diabetes. Compared with those without diabetes, patients with diabetes were less likely to receive adjuvant chemotherapy (crude rate: 58.9% and 49.8%; adjusted percentage point difference: 4.7% [95% confidence limits: 1.7, 7.5]). Mediation analysis indicated that postoperative complications explained 9.4% of the association between diabetes and adjuvant chemotherapy implementation. Conclusions: Our findings suggest that patients with stage III CRC and diabetes are less likely to receive adjuvant chemotherapy than those without diabetes, and postoperative complications may partially account for the association. Key messages: Concomitant diabetes might negatively impact the implementation rate of adjuvant chemotherapy in patients with stage III CRC.